2016
DOI: 10.1038/ncomms12728
|View full text |Cite
|
Sign up to set email alerts
|

Strong cooperative coupling of pressure-induced magnetic order and nematicity in FeSe

Abstract: A hallmark of the iron-based superconductors is the strong coupling between magnetic, structural and electronic degrees of freedom. However, a universal picture of the normal state properties of these compounds has been confounded by recent investigations of FeSe where the nematic (structural) and magnetic transitions appear to be decoupled. Here, using synchrotron-based high-energy x-ray diffraction and time-domain Mössbauer spectroscopy, we show that nematicity and magnetism in FeSe under applied pressure ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
160
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(186 citation statements)
references
References 36 publications
24
160
0
1
Order By: Relevance
“…Besides, FeSe possesses an electronic nematic order after a tetragonal-to-orthorhombic structural transition at T s 90K [19][20][21][22] . Although the primary origin of this nematic order is still unclear [23][24][25][26][27][28][29][30][31][32][33][34] , neutron scattering measurements indicate the important role of spin degree of freedom 24,25 . These novel properties have triggered wide interests in the magnetic ground state of FeSe [35][36][37][38][39][40][41][42][43][44][45] .…”
Section: Introductionmentioning
confidence: 99%
“…Besides, FeSe possesses an electronic nematic order after a tetragonal-to-orthorhombic structural transition at T s 90K [19][20][21][22] . Although the primary origin of this nematic order is still unclear [23][24][25][26][27][28][29][30][31][32][33][34] , neutron scattering measurements indicate the important role of spin degree of freedom 24,25 . These novel properties have triggered wide interests in the magnetic ground state of FeSe [35][36][37][38][39][40][41][42][43][44][45] .…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that applying pressure to FeSe leads to the onset of magnetism [18][19][20], reportedly the CAFM phase [21]. Comparing with Fig.…”
Section: Dynamical Spin-structure Factor and Comparison With Expermentioning
confidence: 80%
“…Since the Néel phase has not been observed in either iron pnictides or chalcogenides, our calculations support the conclusion that K 2 must be present and negative. Above a certain critical value of K 1 , the FQ order is stabilized and a direct transition between the FQ and CAFM phases is achieved [25], mimicking the experimentally observed transition from the nonmagnetic to the antiferromagnetic state in FeSe under applied pressure [18][19][20][21]. For sufficiently large J 3 , a DS magnetic order is obtained in Fig.…”
Section: Phase Diagramsmentioning
confidence: 90%
See 2 more Smart Citations